Pengabdian Kepada Masyarakat melalui Kuliah Kerja Nyata (KKN) dalam Membangun Daerah yang Berkelanjutan di Kelurahan Indrasakti Kecamatan Air Putih - Rahayu, Yayuk Putri; Fatikasari, Cilki; Oktavia, Sri Rahayu; Tusaddiah, Ria; Winata, Ageng Tegar; Harahap, Azmi Kurniawan (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
Community Service (PKM) through Real Work Lecture (KKN) was carried out in Indrasakti Village, Air Putih District, Batu Bara Regency, North Sumatra. This activity aims to increase the role of lecturers and students in providing socialization, education, and improving the entrepreneurial spirit, as well as developing community skills towards sustainable regional development. The methods used are socialization, education and skills training on making used cooking oil soap, making organic waste ecoenzymes, implementing clean and healthy living (PHBS), making MSME financial records, public health checks, and environmental cleanliness mutual cooperation. The stages of this activity are survey and collaboration with the village head; preparation; and counseling, socialization, and education in delivering materials. The results of this PKM KKN activity show an increase in community knowledge and skills with an average knowledge score of 42.5 increasing to 75.8. The conclusion of this activity was an increase in community knowledge and skills by 78.43% which had an impact on improving the quality of life and sustainable regional development in Indrasakti Village.